Référents, Sens Et Effets De Sens De L’énoncé « Vieux Père, Voilà Ton Petit / Tes Petits » Dans Le Français De Côte d’Ivoire - Gnato Sia Modeste (European Scientific Journal, ESJ, 2018)
In Côte d'Ivoire, as elsewhere in the French-speaking world, the French language is characterized by a constant movement on the lexical and semantic level. This situation, which testifies to the dynamism of French in a foreign context, is a constant source of thought for linguists. The present study focuses on the statement Old Father, this is your little one, a recurring expression in the Ivorian conversational landscape. Using the tools and methods of structural grammar and grammar of meaning, the analysis brings out the referential dimension, the meaning and the sense effects subsequent to the use of this utterance.The study shows that, contrary to the standard meaning which indicates a simple presentation of individuals in the same discursive environment, in the Ivorian context, the statement evokes two opposite social classes: on the one hand, the category of old fathers and the other that of the little ones. In addition, the statement covers several values: the comparison of two social classes involved, the evocation of a fake filiality, the axiological values of self-pity and of request.